PEMBINAAN TARTIL AL-QUR’AN METODE TILAWATI DI IBU - IBU AISYIYAH RANTING JOGODALU BENJENG GRESIK - Muyasaroh Muyasaroh (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
This dedication is motivated by the urgency of reading the Qur'an as part of Muslim worship« وَاٌلَذِي يَقُراٌ القُرانَ وَيَتَتَعتَعُ فِيه وَهُوَ عَلَيهِ شَاقٌ لَه اَجَران » متفقٌ عليهRasulullah said, "And the one who reads the Qur'an, while he is still stammering and heavy in reading it, then he will get two rewards." (HR. Bukhari Muslim)In addition, reading the Qur'an must be correct, in accordance with the rules of tajwid science and tartil.The term tartil is interpreted as reading the Al- Qur'an to be calm and slow, with clear letters and waqafs. It can also be interpreted as reading correctly according to the rules of makharijul huruf and their Tajwid. The fact is that not all Aisyiyah members of the Jogodalu branch can read the Qur'an with tartil and according to the rules of tajwid science. Oriented to this problem, the community service activity is in the form of fostering the Practice of Tartil Al-Qur'an Tilawati Method in Aisyiyah Twigs, Jogodalu Village, Benjeng District, Gresik Regency. The purpose of the service is to realize reading the Qur'an in a tartil manner, which is in accordance with the rules of tajwid science and makhorijul huruf. Methods of coaching and mentoring practice using the Lesson study method, namely: Plan, Do and Reflect. in the activity, the Do stage (providing Makhorijul huruf and recitation material as well as mentoring the practice of reading the Al-Qur'an with the tilawati method which is followed by all administrators and members of Mrs. Aisyiyah) then the Reflection/see stage, namely the evaluation of the tartil al-Qur'an with the tilawati method as a group as well as evaluation of service activities. The outcome of the service is the increased competence in reading the Al-Qur'an for women of Aisyiyah Jogodalu Branch as well as the output of scientific articles in journals that are accredited by Sinta according to the output of mandatory service